Has the International Treaty been published? - A. V. Didikina (Московский журнал международного права)
Publication of the international treaty (bringing to the public) is a necessary condition of its application on the territory of the Russian Federation. At the same time that procedure serves the purposes of maintenance of legal certainty and protection of rights and freedom of physical and legal bodies because only after publication of the act it becomes accessible to the interested person who obtains an opportunity to get acquainted with it and conform their behavior to it. But despite the considerable role of that question not much attention has been paid to it. That leads to the occurrence of some substantial problems in practice: when and in what editions is it necessary to publish international treaties, on what bodies the corresponding duties has been imposed. Also within the framework of the article there is an analysis of one legal action in which the problem of appropriate publication of the international treaty has risen especially sharply. The possibility of occurrence of such situations affects the authority of the Russian Federation in the international arena that shows to a great extent the necessity to study that problems and taking measures for their resolution.